The mechanism of miR-16-5p protection on LPS-induced A549 cell injury by targeting CXCR3. Issue 1 (4th December 2019) - Liu, Guo-Pan; Wang, Wei-Wei; Lu, Wen-Ying; Shang, An-Quan
Abstract: Objective: To study the effect of miR-16-5p on lung cancer cell injury and apoptosis, and its mechanism. Methods: LPS induced lung cancer cell A549 injury; qRT-PCR method was applied to detect the expression of miR-16-5p and CXCR3 in A549 cells. Con (without LPS treatment), LPS + miR-NC group (transfected negative control samples), LPS + miR-16-5p group (transfected miR-16-5p mimics); LPS + si-NC group (transfected negative control samples), LPS + si-CXCR3 group (transfected si-CXCR3); LPS + miR-16-5p + pcDNA3.1 group (co-transfected miR-16-5p mimics and pcDNA3.1), LPS + miR-16-5p + pcDNA3.1-CXCR3 group (co-transfected miR-16-5p mimics and pcDNA3.1-CXCR3) were transfected into A549 cells by liposome method. Western blot was used to detect protein expression of CXCR3, IL-6 and TNF-α in A549 cells; apoptosis of A549 cells was detected by flow cytometry. Results: Compared with the control group, the expression of miR-16-5p mRNA was significantly decreased in A549 cells in LPS group, and the mRNA and protein expression of CXCR3 were significantly increased ( p < .05). Overexpression of miR-16-5p and knockdown of CXCR3 both can down-regulated protein expression of IL-6 and TNF-α, and up-regulated apoptosis in LPS-induced A549 cell; CXCR3 is a target of miR-16-5p. Overexpression of CXCR3 rescued the protective effect of miR-16-5p on LPS-induced A549 cell injury. Conclusion: miR-16-5p can protect LPS-induced A549 cell injury, and its mechanism may be related to the targeted regulation of CXCR3, which could provide a new target for targeted therapy of lung cancer.